The Methodology of Contemporary Gender Interpretation: A Study of QirÄâ€™ah MubÄdalah - Taufan Anggoro (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
The various interpretive products that have been offered by previous feminist figures are not followed by an interpretation methodology for gender equality topics. In response to this, qirÄâ€™ah mubÄdalah, an interpretation methÂoÂdoÂlogy of â€˜made in Indonesiaâ€™products which are specifically related to gender and women's issues emerged. To explore more deeply, this study focuses on two things, namely how the interpretation methodology is adopted in the mubÄdalah and how the position of the qirÄâ€™ah mubÄdalah is among the ideas or thoughts of previous feminist figures. Through the descriptive-analytical method, this study seeks to decipher the mubÄdalah in terms of the methodology of interpretation. The hermeneutical analysis is used to study the extent to which operational forms of hermeneutics appear in the mubÄdalah. The result first, methodologically the mubÄdalah shows the existence of operational forms of hermeneutics, with more emphasis on efforts to explore context and conÂtexÂtualization. Second, compared to previous feminist thinkers, the methodology of interpreting the qirÄâ€™ah mubÄÂdalah is more soft, systematic and applicable in its application. Besides, qirÄâ€™ah mubÄdalah is also classified as a progressive interpretation, which is essentially based on the concept of monotheism and the reciprocal method.